Age- and health-related quality of life after total hip replacement. (June 2014) - Gordon, Max; Greene, Meridith; Frumento, Paolo; Rolfson, Ola; Garellick, Göran; Stark, André
<x xml:space="preserve">Abstract</x> Background — While age is a common confounder, its impact on health-related quality of life (HRQoL) after total hip replacement is uncertain. This could be due to improper statistical modeling of age in previous studies, such as treating age as a linear variable or by using age categories. We hypothesized that there is a non-linear association between age and HRQoL. Methods — We selected a nationwide cohort from the Swedish Hip Arthroplasty Register of patients operated with total hip replacements due to primary osteoarthritis between 2008 and 2010. For estimating HRQoL, we used the generic health outcome questionnaire EQ-5D of the EuroQol group that consits or 2 parts: the EQ-5D index and the EQ VAS estimates. Using linear regression, we modeled the EQ-5D index and the EQ VAS against age 1 year after surgery. Instead of using a straight line for age, we applied a method called restricted cubic splines that allows the line to bend in a controlled manner. Confounding was controlled by adjusting for preoperative HRQoL, sex, previous contralateral hip surgery, pain, and Charnley classification. Results — Complete data on 27, 245 patients were available for analysis. Both the EQ-5D index and EQ VAS showed a non-linear relationship with age. They were fairly unaffected by age until the patients were in their late sixties, after which age had a negative effect. Interpretation — There is a non-linear relationship between age and HRQoL, with improvement decreasing in the elderly.